Phrynohyas venulosa (Veined Treefrog) diet. - Duré Pitteri, Marta Inés (2006)
Phrynohyas venulosa has a wide distribution in Central and South America, ranging fram the lowlands of Mexico to the Amazon Basin of Colombia, Ecuador, Pero, Venezuela, and Brazi1; the Guianas, Brazil, Paraguay, Trinidad, and Tobago (Frost 2004. http:/ Iresearch.amnh.org/herpetology/amphibia/index.htm1). In Argentina, P.venulosa occurs in Jujuy, Salta, Formosa, Chaco, Corrientes, and Entre Ríos y Misiones (Cei 1980. Amphibians of Argentina. Monitore Zoologico Italiano MS). We examined the stomach contents of20 specimens collected 15 km NW ofCorrientes (27°28'S, 58°50'W), Corrientes, Argentina, between Febroary 1994 and March 1999. Only 35% (N = 7) had identifiable stomach contents (males: 64.4 ± 16.3 mm SVL, N = 3; females: 76.6 ± 5.7 mm SVL,N=4).